Conjunctivitis among Rural and Urban School Children in Erbil Governorate/ Iraq - Nabaz Fisal Shakir Agha (Diyala Journal of Medicine, 2020)
Background: In children conjunctivitis is the most widespread ocular surface disease. It is referred to any inflammatory condition of the conjunctiva. Conjunctivitis was the most common associated comorbidities that had an influence on the health of children.